Ks. Wacław Sierakowski – propagator wiedzy o muzyce i organizator szkolnictwa muzycznego w okresie działalności Komisji Edukacji Narodowej - Piekarski, Michał (Biuletyn Historii Wychowania, 2016)
In the second half of the 18th century, musical education in Poland was poor. The Commission of National Education (1773–1793) did not take music into account in its projects. The individual willing to change the situation was Father Wacław Sierakowski (1741–1806), provost of the Wawel Cathedral in Krakow. He played a significant role in the musical life of the city as an organiser of public concerts and founder of a private music school. In 1795–1796, he published a three-volume musical textbook, The Art of Music for Young Polish People (Sztuka muzyki dla młodzieży krajowej), one of the first musical textbooks in the Polish language. In Sierakowski’s publication the stress was put on the social and national value of music. The first volume also featured Sierakowski’s petition from 1792, intended for submission before the Sejm (Polish Parliament), in which the author propounded the idea of the state taking over musical education and establishing a major statesponsored music school in Krakow (Alumnatus Vocalistarum). These plans were never carried out as the third partition of Poland ensued in 1795.